EXPLOITATION OF WOMEN IN THE CHANGING POWER DYNAMICS - Meldianto, Redni Putri; Hanida, Rozidateno Putri; Hasnita, Siska Surya (Jurnal Governansi, 2024)
This research examines the role of women in political oligarchy and their potential to change power dynamics. Political oligarchy concentrates power in the hands of a few, often overlooking women's roles within this structure. Feminist intersectionality reveals that social class significantly influences women's involvement in oligarchy, with greater barriers for women from lower economic classes. Women's participation in politics, both as leaders and members of political parties, is crucial for representing their unique needs in policy-making. However, women in decision-making roles often face cultural and normative dilemmas, needing to overcome negative stereotypes. The feminist movement plays a vital role in addressing gender inequality by changing cultural norms and raising awareness of gender bias. Although the Constitution of Indonesia and international conventions affirm gender equality, implementation requires specific policies. This research employs a qualitative descriptive method, collecting data from literature, official documents, and news sources. Findings indicate that women's roles in political oligarchy are often tied to kinship relations, political clans, and dynasties. Despite affirmative action policies promoting 30% female representation in legislative candidate lists, this representation often serves to validate the interests of certain groups. Nonetheless, women's involvement in politics is a positive step toward gender equality. Addressing gender inequality and increasing women's participation in decision-making requires robust efforts to support women's rights and dismantle social and political barriers. Further policy implementation to support women's political representation is essential for a more inclusive and gender-equal society.